The religious, over religious, nonreligious or antireligious face in the national Albanian awakening, 1878–1918? - Szczepański, Wojciech (Balcanica Posnaniensia. Acta et studia, 2010)
The aim of the article is to analyze the role of religion in the Albanian National Awakening (Rilindja Kombëtare) of 1878–1918 and to determine whether this process had a religious, over-religious, nonreligious, or anti-religious character. The author draws attention to the often-overlooked religious dimension of the Albanian national movement, which largely developed within a multi-confessional society under Ottoman rule. The study employs a comparative analysis of historical, literary, and journalistic sources, including the works of Pashko Vasa and the Frashëri brothers, as well as historical studies on the League of Prizren and later national initiatives. The findings indicate that, although religion was an important component of Albanian identity, it did not constitute the foundation of the national movement. On the contrary, the leaders of Rilindja-Muslims, Catholics, and Orthodox Christians alike-sought to construct a supra-confessional idea of national unity, based on a shared language, traditions, and historical memory symbolized by the figure of Skanderbeg. In this context, Pashko Vasa’s famous dictum „the religion of Albanians is Albanianism” expressed an aspiration for national consensus beyond confessional divisions rather than a rejection of faith. The author concludes that the Albanian National Awakening was neither anti-religious nor nonreligious, but rather over-religious. Rilindja represents a conscious synthesis of national ideas and respect for religious diversity, enabling the Albanians to build the foundations of a modern national community despite clear denominational differences.